2020
DOI: 10.1192/bjo.2020.27
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and clinicians’ perspectives on relevant treatment outcomes in depression: qualitative study

Abstract: Background Although symptomatic remission is considered the optimal outcome in depression, this is not always achieved. Furthermore, symptom indicators do not fully capture patients’ and clinicians’ perspectives on remission. Broader indicators of (partial) remission from depression should be considered. Aims To investigate relevant outcomes of depression treatment in specialist care from patients’ and clinicians’ perspectives and to investigate whether these perspectives differ from eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Clinician-rated scales, such as the Montgomery-Åsberg Depression Rating Scale or the Hamilton Depression Rating Scale, are often used to assess the efficacy of antidepressant treatment in clinical trial settings, while the Functioning Assessment Short Test (FAST) may be used for the clinical evaluation of functional impairment in patients with MDD. However, clinician-rated scales may not fully capture a patient's subjective experience of MDD and antidepressant treatment, and patients' perceptions of symptoms and treatment outcomes in MDD have been shown to differ from those of their clinicians (76)(77)(78)(79)(80). Furthermore, most clinician-rated scales that are short, easy and applicable for routine care are interview-based.…”
Section: Discussionmentioning
confidence: 99%
“…Clinician-rated scales, such as the Montgomery-Åsberg Depression Rating Scale or the Hamilton Depression Rating Scale, are often used to assess the efficacy of antidepressant treatment in clinical trial settings, while the Functioning Assessment Short Test (FAST) may be used for the clinical evaluation of functional impairment in patients with MDD. However, clinician-rated scales may not fully capture a patient's subjective experience of MDD and antidepressant treatment, and patients' perceptions of symptoms and treatment outcomes in MDD have been shown to differ from those of their clinicians (76)(77)(78)(79)(80). Furthermore, most clinician-rated scales that are short, easy and applicable for routine care are interview-based.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients were significantly more likely than HCPs to think that psychological trauma was a reason for their depression and that their depression was more severe because of it. Other studies have shown clinically relevant differences between patient and HCP perceptions of depression [ 45 47 ]. Nevertheless, the possibility that patients may have overestimated the potential impact of their experience of psychological trauma on their depression cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with other research that has been conducted into the bothersome symptoms and impact of MDD on the lives of patients. 21 , 25–29 …”
Section: Discussionmentioning
confidence: 99%